(3bQGAGJ fXQjI hJeGQjf JWHjbjI s - (3BSjG(B, (3TQjas ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2015)
(3jMJhj gPG GdcJGH Ydi SJI aUhd MjK jHOC eaghe GdOjeZQGajG hCgejJgG heUGOQ LeY GdeYWjGJ, OQGSI GdXhGgQ GdOjeZQGajI hWQb bjGSgG ef haGJjI, RhGLjI, hdGOjI, NUhHI, JcGKQ, hGNJJe GdcJGH HeLehYI ef GdJeGQjf GdeMdhdI (B.s
(3GdedGMb U(B.213 (3GdeQGLY U(B. 216s
Keywords: (3GdOjeZQGajGs; (3Gdfeh GdScGfjs